KIDCOPE-Child in Bahasa Malaysia: A Study on Psychometric Properties among the Paediatric Population - Norsuhana Emilinadiah Husin (N/A, 2023)
KIDCOPE-Child in Bahasa Malaysia: A Study on Psychometric Properties among the Paediatric Population by Norsuhana Emilinadiah Husin